An experimental design of a robotic delivery company - Foo, Melvin Maw Qing (Nanyang Technological University, 2024)
This FYP focuses on the development of delivery robots for a startup company. The objective of the project is for a student who wants to establish his/her company after graduation. The project created a robotic delivery company and piloted a Robotic Delivery as a service (DaaS) on the NTU campus. The startup aims to reduce cost for users, increase profitability for businesses and improve quality of life for logistics workers. This report details technical and business details of the startup. Listed below are requirements of the project: